The fishing life : quirky tales of angling adventures, mishaps, and memories - Schullery, Paul (Skyhorse Publishing, 2013)
"An anthology of fishing anecdotes, well-researched articles, and dreamlike musings about being a fisherman and living the fishing life"--Provided by publisher.